Protocol for a qualitative study exploring older adults’ experience of mental health and wellbeing in work-related later life transitions in the UK - Rebecca Woodhouse; Dean McMillan; Ruth Wadman (PLoS ONE, 2026)
Later life transitions occur in the later years of life and can cause significant disruption to a person’s usual daily routine and lifestyle. Transitions that are specifically related to work, such as retirement, can cause sudden changes to an individual’s financial, social and psychological environment and for some, may negatively impact on mental health and wellbeing. This protocol outlines a qualitative study to explore the experiences of adults in the UK, who have experienced a negative impact on their mental health or wellbeing due to a work-related transition in later life. Semi-structed interviews will be completed with people aged 50 and over to gain a deeper understanding of 1) the mental health and wellbeing of people undertaking later life transitions; 2) the context surrounding the transitions (such as due to ill-health or redundancy); and 3) the types of support they received or may have benefitted from. Research in this area is scarce and this study will help us to better understand the experience of those who have encountered such difficulties to help develop appropriate interventions and support in this area.